Consórcio de milho com Urochloa ruziziensis em dois espaçamentos e modalidades de semeadura - Queiroz, Renata Fernandes de (2015)
The no tillage system (SPD) is a conservation practice that aims to more sustainable production system and is able to be reproduced in large areas of land. The maize grown in SPD says the culture of compatibility in consortium with forage, mainly with fodder generic taxon Urochloa that have great potential for the production of straw without interfering in grain production. The objective of this study was to identify the appropriate spatial arrangement for the maize crop in consortium with Urochloa ruziziensis taking into account productive aspects of grain, straw and operating the mechanized sowing system. The experiment was conducted experimental area of the Laboratory of Machines and Agricultural Mechanization of UNESP / Jaboticabal- SP, in Rhodic Eutrudox, clayey in the period from January to July of 2014 with experimental design randomized blocks with eight treatments in scheme factorial 2x3 + 2, with four repetitions. The treatments consisted of two spacings of maize (0.45 and 0.90 m) and three types of Urochloa ruziziensis consortium with corn (Urochloa sown at line; Urochloa throwing sowing at the sowing of maize, Urochloa throwing sowing at V4 stage of maize) + Witness (single maize): E1M1- maize spaced 0.45 m intercropped with Urochloa ruziziensis sown at maize line; E1M2 - sown maize on 0.45 m spacing intercropped with Urochloa ruziziensis throwing sowing at sowing of maize; E1M3 - maize sown in 0.45 m spacing with Urochloa ruziziensis sown by broadcasting at V4 stage of maize; E2M1- maize spaced 0.90 m intercropped with Urochloa ruziziensis sown at maize line; E2M2 - sown maize on 0.45 m spacing intercropped with Urochloa ruziziensis throwing sowing at sowing of maize; E2M3 - maize sown in 0.90 m spacing with Urochloa ruziziensis sown by broadcasting at V4 stage of maize; T1 - single maize sown in the spacing of 0.45 m; T2 - single maize sown in the spacing of 0.90 m. The results showed that intercropping maize to 0.90 m with Urochloa ruziziensis at sowing line provided better grain production results without interfering with the production of plant dry matter of Urochloa and getting better results for the operating conditions of mechanized sowing.